ANALISA EFEKTIFITAS PROMOSI TERHADAP KEPUTUSAN KONSUMEN PADA MEMBELI SEMEN BARURAJA DI KELURAHAN SEKIP JAYA KECAMATAN KEMUNING PALEMBANG - Luis Marnisah; Denny Saputra; Azra’ie K Rosni (Jurnal Ilmiah Ekonomi Global Masa Kini)
In order to obtain information to determine the influence of promotion mix to the consumer’s decision to buy cement Balfour in the village Sekip Jaya subdistrict Kemuning Palembang, the population in this study are all people who lived in the village Sekip jaya subdistrict Kemuning Palembang while the sample used is random sampling where from random sampling the obtained 100 respondents, the question in this study using three indicators, namely promotion mix of advertising, sales promotion, and public relations. The method used is the method of test validity, reliability testing, regression, hypothesis testing, and test normalization. Bassed on research on the promotional mix towards the consumer’s decision to buy cement Balfour in Sub Sekip Jaya Subdistrict Kemuning Palembang by using the above it can be concluded that the promotion mix influence consumer’s decision to buy cement Balfour in Sub Sekip Jaya subdistrict Kemuning Palembang and indicators promotion mix greatest influence decisions purchase is advertising.Keyword: Promotion Mix Influence On Purchasing Decisions